The Effectiveness of Outdoor Learning-Based Teaching Methods in Enhancing the Understanding of Geographic Concepts - Krissi Wahyuni Saragih; Satria Chandra; Sinta Rahayu Saragih (CAKRAWALA: Journal of Citizenship Teaching and Learning, 2025)
This study aims to examine the effectiveness of the outdoor learning-based teaching method in improving the understanding of geographic concepts among eleventh-grade students at SMA Negeri 1 Dolok Pardamean, Simalungun Regency, North Sumatra. The study employed a quantitative approach with a quasi-experimental design using the nonequivalent control group design, involving two groups: the experimental group taught through the outdoor learning method and the control group taught through conventional methods. The research instruments consisted of written tests and observation sheets. Data were analyzed using descriptive statistics and a t-test to determine significant differences between groups. The findings revealed a significant improvement in students’ understanding of geographic concepts when taught through the outdoor learning method. The average posttest score of the experimental group reached 82.70, higher than that of the control group, which was only 74.15. The t-test result showed a t-value of 4.52 with a significance level of p < 0.001, confirming a significant difference between the two groups. Observations also indicated that student engagement in the experimental group was higher (85%) compared to the control group (60%), suggesting that this method is effective in enhancing students’ motivation and participation.